A Qualitative Study of Iranian Parents' Experiences of Interacting With Their Adolescent Children. (November 2019) - Rahkar Farshi, Mahni; Valizadeh, Leila; Zamanzadeh, Vahid; Rassouli, Maryam; Lees, David; Lopez, Violeta; Cleary, Michelle
Introduction: Transition from childhood to adulthood is an important and challenging period for both adolescents and their parents, particularly in societies undergoing development and change. In Iran, cultural and social change is inextricably linked to, and strongly impacts on, family units.Aim: To explore the experiences of parents and the strategies they use in interacting with their adolescent children.Method: Qualitative descriptive research using in-depth interviews was conducted with 23 parents of adolescents in Iran. Transcribed data were subjected to thematic analysis.Results: Parents used two key approaches to effectively interact with their adolescent children. The first, "transformed parenting" involved the parents changing their parenting style and practices. The second approach, "child orientation" involved the parents trying to control, educate, and guide their child.Implication for transcultural practice: Understanding how parents experience interactions with adolescents in the context of Iranian culture and increasing modernity will guide nurses to foster effective parenting strategies for optimal adolescent development.